Proteomic and Transcriptomic Analyses Indicate Reduced Biofilm-Forming Abilities in Cefiderocol-Resistant Klebsiella pneumoniae - Bao, Jinfeng; Xie, Lu; Ma, Yating; An, Ran; Gu, Bing; Wang, Chengbin (Frontiers in Microbiology, 2022)
The advent of cefiderocol provides hope for the clinical treatment of multi-drug resistant gram-negative bacteria, especially carbapenem resistance. The resistance ability of Klebsiella pneumoniae to cefiderocol can be dramatically improved by acclimatization. In the present study, we collected cefiderocol resistant Klebsiella pneumoniae from a 36-day acclimatization by increasing the cefiderocol concentration in the culture medium to investigate its biological characteristics changes and the internal mechanismat at the level of proteome and transcriptome. The decrease of biofilm formation ability was the main biological characteristic change of the inducible strain. Downregulation of biofilm formation proteins (genes) including hdeB, stpA, yhjQ, fba, bcsZ, uvrY, bcsE, bcsC and ibpB were the main factors that reduced the biofilm formation ability. Moreover, the down regulation of siderophore transporters proteins including iron uptake system component efeO, tonB-dependent receptor fecA, and ferric iron ABC transporter fbpA may be one of the determination factors leading to cefiderocol resistance and promoting the reduction of biofilm formation ability of Klebsiella pneumoniae. To the best of our knowledge, this is the first study to investigate cefiderocol resistance based on proteomic and transcriptomic technique.